O quarto e a criança : linha de mobiliário lúdica como auxílio ao seu desenvolvimento - Cardoso, Tiago (2018)
Children have an ability of imagination that can make dreams come true, make cars fly, give life to a broomstick and turn it into a horse. This whole universe is only possible if the child is continuously being monitored and learning from birth. When children observe things, this allows a better development and give them the ability to distinguish good from less good, right and wrong. The theme which defines this research aims to develop equipment for the proper growth of children in their spaces, since the infancy stage, particularly the bedroom. This set of equipment plays a crucial role in the preoperative phase from 3 to 6 years old. For this subject, the study of materials on the child is being regarded, as well as examining the characteristics and needs which deserve full attention in this preoperative period. The concept of playing as a need for children in the first years of life will also be analyzed, being intrinsically related to the toy. Furthermore, this highlights throughout the work. These tools will be very useful to collaborate in the creation of a completely renovated space for children. Questionnaire findings to 16 children’s bedrooms with different characteristics will be presented, in order to find out their tastes and parents’ concerns about their children. Following, a survey of existing cases in the market will be carried out, so that they may be analyzed to identify strengths and weaknesses, as an aid to the project which will be built up. Finally, through the mentioned tools, the set of equipment will be presented, named as play-functional furniture line. It aims to help improve the child's motor, psychosocial, artistic and cognitive abilities, enhancing their development and well-being